1993
DOI: 10.1002/jbmr.5650081106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the skeletal effects of combined mild dietary calcium restriction and ovariectomy in sinclair S-1 minipigs: A pilot study

Abstract: A pilot study was conducted to investigate the combined effects of ovariectomy (OVX) with preceding and concomitant mild dietary calcium restriction on the minipig skeleton. Minipigs 4 months old were fed diets containing 0.9, 0.75, or 0.5% calcium (Ca). At 10 months, the 0.75 and 0.5% pigs were OVX and the 0.9% were either sham operated or OVX. All pigs were maintained on their respective diets for an additional 6 months. Excised lumbar vertebrae and long bones were evaluated by densitometry and histomorphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 30 publications
0
17
0
6
Order By: Relevance
“…The rate of bone removal and deposition of the trabecular and cortical bone is also similar to that observed in humans (Mosekilde et al, 1993b). A porcine model has also been used to evaluate the initial fixation strength of a biodegradable interference screw in Litten-Brown, Corson and Clarke anterior cruciate ligament reconstruction using a bone-patellar tendon-bone graft (Seil et al, 1998;Walsh et al, 2009).…”
Section: Bonesmentioning
confidence: 67%
See 1 more Smart Citation
“…The rate of bone removal and deposition of the trabecular and cortical bone is also similar to that observed in humans (Mosekilde et al, 1993b). A porcine model has also been used to evaluate the initial fixation strength of a biodegradable interference screw in Litten-Brown, Corson and Clarke anterior cruciate ligament reconstruction using a bone-patellar tendon-bone graft (Seil et al, 1998;Walsh et al, 2009).…”
Section: Bonesmentioning
confidence: 67%
“…Findings suggest that the Sinclair Si minipig fed a 0.75% calcium restricted diet may be a good model to study the bone remodelling and perimenopausal bone loss in women when an ovariectomy is performed (Mosekilde et al, 1993a and1993b;Boyce et al, 1995). Lafage et al (1995) have also used minipigs to investigate bone active agents such as sodium fluoride, assessed on bone quality and remodelling.…”
Section: Bonesmentioning
confidence: 99%
“…However, the time required to establish an accurate osteoporosis model remains inconsistent between studies. A number of previous studies (20)(21)(22)(23) have found that bone formation in sheep continues to decline between 10 weeks and 6 months after an ovariectomy, with certain studies reporting that the BMD significantly decreases 6 months after an ovariectomy (24); however, other studies have not observed these results (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that minipigs are comparable to NHP in immunogenicity testing [158,159] and their liver metabolism is similar to that of humans [160]. Additionally, models of porcine osteoporosis have been developed to expand the usefulness of this species for bone research [161][162][163][164].…”
Section: Pigmentioning
confidence: 99%